ANALISIS MANAJEMEN WAKTU DALAM QS. AL-‘ASHR : STUDI KOMPARASI TAFSIR AL-MISBAH DAN TAFSIR AL-AZHAR - Nurul Fadilah; Hamidullah Mahmud (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
This research is motivated by the importance of time in the Qur'an, especially through Surah Al-'Ashr. This research compares Tafsir Al-Misbah by Mohammad Quraish Shihab and Tafsir Al-Azhar by Hamka, providing an opportunity to understand various dimensions of time management from an Islamic perspective. Both interpretations can provide different insights. The purpose of this research is to compare the analysis of time management in QS AL-'Ashr in the interpretations of Al-Misbah and Al-Azhar. Then this research uses a literature study method using a qualitative descriptive approach. This method is a research method by collecting information or data through journals, books, notes, interpretations with other sources. The results of this study explain that Tafsir Al-Misbah and Tafsir Al-Azhar do have important contributions to the tradition of interpretation in Indonesia, with different characteristics. Similarities: 1) the purpose of interpretation: both aim to provide a deep understanding of the Qur'an as a guide to life; 2) interdisciplinary approach: integrating various disciplines to expand the meaning of the verse; 3) the use of references: referring to classical sources and scholarly opinions, showing commitment to the scientific tradition; 4) social and cultural influences: linking the teachings of the Qur'an with the social and cultural context of society. while for the differences: 1) author and background: al-misbah was written by muhammad quraish shihab with a narrative approach, while al-azhar by buya hamka with a focus on fiqh issues; 2) thematic approach: al-misbah is more thematic and reflective, while al-azhar is systematic and analytical; 3) language style: al-misbah uses poetic language, while al-azhar is more formal and academic; 5) context focus: al-misbah emphasises Indonesian social and cultural issues, while al-azhar is more on religious and legal contexts